5th International Conference on the Engineering of Sport in Davis, California, USA (2004)
The 5th Conference in September 2004 was held at Davis, California, USA. Organised by Professor Mont Hubbard, Dr Rabi Mehta and Dr Jani Macari Pallis the Conference was held on campus at Davis , where 173 papers were presented to delegates from more than 15 countries. The conference witnessed a 50% growth in the number of papers and a broadening of participation to include more industrially affiliated engineers and scientists.